Inflation and trade openness revised: An analysis using panel data - Adolfo Sachsida; Mário Jorge Cardoso de Mendonça (Institute for Applied Economic Research (ipea), 2015)
In this article we estimate the relationship between inflation and trade openness [e.g., Romer (1993)] using modern panel data techniques. The advantage here is that we are able to explicit test the hypothesis proposed by Terra (1998) that the negative relationship between openness and inflation is due to severely indebted countries in the debt crisis period. The econometric results give support to Romer (1993) showing that the negative relationship between inflation and openness are neither restrict to a subset of countries or a time period.
Keywords: C23; E61; 330